Resolution via Diastereomeric Salt Crystallization of Ibuprofen Lysine: Ternary Phase Diagram Studies. Issue 5 (25th March 2018) - Simon, Melba; Donnellan, Philip; Glennon, Brian; Jones, Roderick C.
Abstract: Numerous pharmaceutical ingredients are chiral and generally only one isomer shows the desired therapeutic activity. Therefore, enantioseparation, e.g., by crystallization, is a key step in the pharmaceutical industry. In this work, ternary phase diagrams of the diastereomeric salt formation of ibuprofen lysine in aqueous ethanol are generated. The solubilities of the formed diastereomeric salts are measured in a defined temperature range. Investigation of the X‐ray powder diffraction patterns confirmed ibuprofen lysine as a simple eutectic system in agreement to the previously reported observations. The metastable zone widths of diastereomeric salt pairs of ibuprofen lysine are discussed with a resolution procedure proposed using the phase diagram that achieves maximum possible yield. Abstract : Crystallization is widely applied to eliminate enantiomeric impurities. The optimal resolution of a diastereomeric salt is highly dependent on the solid‐liquid phase diagrams of the two salts. The thermodynamic and kinetic properties of ibuprofen lysine diastereomeric salt were investigated. A design procedure was postulated to obtain pure salts with the highest possible yield.